Hypotyposis in Kant's Metaphysics of Judgment Symbolizing Completeness. - Clugston, Byron Ashley (Contemporary Studies in Idealism., 2019)
In demonstrating how much Kant's metaphysics of judgment relies on symbolism, this book clarifies Kant's relationship to Romanticism. This connection sets the stage for an argument against the rational/irrational dichotomy.